Trends of disturbance of Volga-Ural steppe landscapes in oil-and-gas production and approaches to land use optimisation solutions - Myachina, K V; Ryabuha, A G (IOP conference series. Earth and environmental science, 2019)
We study the factors and tendencies for a technogenic disturbance of Volga-Ural steppe region landscapes exposed to the influence of oil-and-gas production. The study area is 1500km2, including landscapes of more than 25 oil-and-gas fields with a various time of development and different alternatives and scales of technogenic impact. Survey of landscapes is as a part of the regional geo-ecological analysis, which incorporates the analysis of a group of natural factors that specify the attributes of the steppe zone, and classification and identification of the most large-scale and widespread environmental problems. We present the recommended algorithm for making a regional geo-ecological analysis which incorporates the ways, methods, and approaches to achieving ecological-subsoil-user balance in oil-and-gas production areas We show that such environmental problems as haphazard expansion of disturbed lands, fragmentation of landscapes, change in conditions of water reservoirs, intensification of exogenic processes, creation of temperature anomaly areas, reduction of the number of mammals are most likely to occur within oil-and-gas fields. So-called Technogenic geosystems of oil-and-gas fields form in the landscapes. Knowledge about the specific aspects and regularities in the functioning of these geosystems should be used to create prognostic scenarios of disturbed lands development and target-focused optimisation measures.